ASSESSING NON-ENGLISH DEPARTMENT STUDENTS' MASTERY OF ACADEMIC CONTENT AREA READING - Gunadi H. Sulistyo (Universitas Negeri Malang, 2013)
Abstract: Assessing Non English Department Students' Mastery of Academic Content Area Reading. This study addresses mainly college students'comprehension on academic texts. It involves 400 respondents of three state and three private universities in Malang with study programs with 'high, 'fair', and 'low' bases on the proportion of the study programs accredited A by the National Board of Accreditation (BAN). Quantitative data were analyzed descriptively and comparatively. The results show reading comprehension of most respondents ranges from 'avarage' to 'low'. Most word attack skills and text content attack skills are low. Text structure attack skills are not adequately mastered. The respondents' comprehension across state universities does not significantly differ, but there is a difference across private universities, limited to certain private universities. A significant difference between the comprehension of students of state universities and private universities and a significant difference between the comprehension of science and social studies students are evidenced. Most respondents are not yet ready for academic comprehension of English. Abstrak: Asesmen Kemampuan Membaca Pemahaman Teks Akademik Mahasiswa Non-Jurusan Bahasa Inggris. Penelitian ini bertujuan untuk mengungkap penguasaan keterampilan memahami teks akademik mahasiswa. Penelitian ini menggunakan rancangan expost facto yang melibatkan 400 responden dari tiga PTN dan tiga PTS di Malang yang memiliki proporsi program studi terakreditasi A oleh BAN pada kategori 'tinggi', 'sedang', 'rendah'. Data kuantitatif dianalisis secara deskriptif dan komparatif. Hasil penelitian menunjukkan bahwa tingkat penguasaan keterampilan membaca sebagian besar responden cenderung rendah. Sebagian besar word attack skills masih rendah penguasaannya. Tidak ada satu pun keterampilan text structure attack skills yang sudah dikuasai secara memadai. Penguasaan keterampilan text content attack skills pada umumnya masih tergolong rendah. Juga, tidak ada perbedaan kemampuan mahasiswa lintas PTN. Namun ada perbedaan antara rerata kemampuan responden lintas PTS, meskipun terbatas pada PTS tertentu saja. Ada perbedaan signifikan antara kemampuan mahasiswa dari PTN dan PTS. Ada perbedaan signifikan antara kemampuan mahasiswa dari IPA dan IPS. Sebagian besar responden belum siap untuk memahami teks akademik berbahasa Inggris.